Management and Becoming of Chest Pain of Undetermined Origin After Leaving the Emergency Department - BOURICHE, Fatima; RUF, Aurelia; YVORRA, Serge; MICHELET, Pierre (Cardiology and Cardiovascular Medicine, 2023)
Objectives: This retrospective work made it possible to determine the strategy of intra-hospital, extra- hospital management as well as the future of patients consulting emergency patients for chest pain. Methods: We included 188 patients consulting the emergency and leaving with a diagnosis of chest pain of undetermined origin. Results: We highlighted that 46.8% of these patients returned home without instructions and it was statistically significantly mostly women. 29.3% of our workforce have received a prescription for additional examinations, with a myocardial ischemia assessment to be performed in 55.8%. 73.1% of the patients were observing in the consultation of a city doctor, 70.5% of the examinations prescribed by the hospital were carried out. In total, the cardiovascular origin is not systematically advanced, as much by the hospital structure as by city doctors. Furthermore, 2.7% of patients have felt a major cardiovascular event only with type of acute coronary syndrome. These were exclusively men and statistically significantly men 50 to 75 years. In addition, 25% of the workforce had non-cardiovascular events major, and in this case it was statistically significantly predominantly women, a fortiori women aged 60 to 75 years. Thus, patients returning home with a symptom of chest pain of undetermined origin comprise two populations at risk, men 50 to 75 years of age for major cardiovascular events such as acute coronary syndrome and women 60 to 75 years for non-major cardiovascular events. Conclusion: It seems to emerge from our work that 2 populations are particularly to be monitored and that they could justify better coded exit instructions. In any case, these data are to be confirmed by other superior power and methodology studies.